2019
DOI: 10.1007/s11481-019-09839-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Bruton’s Tyrosine Kinase Modulates Microglial Phagocytosis: Therapeutic Implications for Alzheimer’s Disease

Abstract: Bruton’s tyrosine kinase (BTK), a critical component of B cell receptor signaling, has recently been implicated in regulation of the peripheral innate immune response. However, the role of BTK in microglia, the resident innate immune cells of the central nervous system, and its involvement in the pathobiology of neurodegenerative disease has not been explored. Here we found that BTK is a key regulator of microglial phagocytosis. Using potent BTK inhibitors and small interfering RNA (siRNA) against BTK, we obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 77 publications
(86 reference statements)
1
47
0
Order By: Relevance
“…However, the potential of ibrutinib to modulate the pathology of neurodegenerative diseases such as AD has not been fully addressed. BTK expression is upregulated postmortem in the brains of AD patients and 5xFAD mice (mouse model of AD) (Keaney et al, 2019), and inhibition of BTK suppresses microglial activation and synaptic loss by deactivating PLCγ2 (Keaney et al, 2019). Given that reactive microglia are critical in the pathogenesis of AD, these observations imply that suppression of BTK might be a potential target for regulating AD pathology via inhibition of microglial activation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the potential of ibrutinib to modulate the pathology of neurodegenerative diseases such as AD has not been fully addressed. BTK expression is upregulated postmortem in the brains of AD patients and 5xFAD mice (mouse model of AD) (Keaney et al, 2019), and inhibition of BTK suppresses microglial activation and synaptic loss by deactivating PLCγ2 (Keaney et al, 2019). Given that reactive microglia are critical in the pathogenesis of AD, these observations imply that suppression of BTK might be a potential target for regulating AD pathology via inhibition of microglial activation.…”
Section: Introductionmentioning
confidence: 99%
“…To visualize their engulfment by microglia or astrocytes, SYNs can be stained with dyes sensitive to acidic pH ( 102 104 , 147 ). These dyes (one of the most widely employed is pHrodo) show little or no fluorescent signal at neutral pH, while they fluoresce brightly when in acidic environments, thus allowing SYN visualization only when engulfed by acidic phagosomes.…”
Section: In Vitro and Ex Vivo Engulfmentmentioning
confidence: 99%
“…Using a similar approach, Keaney et al showed that the blockade of Bruton's Tyrosine Kinase (BTK), a protein involved in different processes such as B cell receptor signaling, pro-inflammatory cytokine release and phagocytosis, reduces the uptake of pHrodo-labeled SYNs by microglia ( 102 ). PHrodo labeled SYNs were also used by Madore et al, to show the relevance of poly-unsaturated omega-3 fatty acids (n-3 PUFAs) in controlling microglial phagocytosis in the developing brain.…”
Section: In Vitro and Ex Vivo Engulfmentmentioning
confidence: 99%
“…Of note, additional studies pointed on the use of Bruton tyrosine kinase inhibitors in the treatment of AD as well as in MS (Montalban et al, 2019;Keaney et al, 2019). In addition, cysteine-targeting compounds such as ICE-like cysteine protease inhibitors (caspase I inhibitors) have been recently suggested as anti-apoptotic and anti-inflammatory agents to treat AD and PD patients, in which progressive neuronal death seems to be associated with caspase overactivation (LoPachin et al, 2008).…”
Section: Therapeutic Options For Michael Acceptors For Neurodegeneratmentioning
confidence: 99%